2007
DOI: 10.1097/qad.0b013e32810c8d16
|View full text |Cite
|
Sign up to set email alerts
|

Increased haemoglobin A2 percentage in HIV infection: disease or treatment?

Abstract: An elevated haemoglobin A2 percentage has been reported in HIV-infected patients, possibly attributable to therapy. In cross-sectional and cohort studies we have established that A2 is often elevated in untreated patients; a further rise during treatment is attributable specifically to zidovudine. The haemoglobin A2 may be high enough to lead to a misdiagnosis of beta thalassemia trait if there is a lack of awareness of this unexpected effect of HIV infection and its treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…In the present study, thyroid functions test was within normal limits in both study and control groups. Wilkinson et al observed that incidence of increased Hb A 2 value was significantly high in patients treated with zidovudine containing HAART than in those treated with non-zidovudine HAART and normal volunteers [4]. In the present study all patients on zidovudine containing ART had raised Hb A 2 value than control group.…”
Section: Discussionsupporting
confidence: 48%
“…In the present study, thyroid functions test was within normal limits in both study and control groups. Wilkinson et al observed that incidence of increased Hb A 2 value was significantly high in patients treated with zidovudine containing HAART than in those treated with non-zidovudine HAART and normal volunteers [4]. In the present study all patients on zidovudine containing ART had raised Hb A 2 value than control group.…”
Section: Discussionsupporting
confidence: 48%
“…Increased levels have been reported in the absence of β thalassaemia trait in a few significant cases of hyperthyroidism (values over 4%),14 in HIV-infected patients treated with antiretroviral therapy, 15 16 by Piero Giordano (personal communication), and in the presence of megaloblastic anaemia 17…”
Section: Methodological Aspectsmentioning
confidence: 98%
“… • Re‐analyse FBC • Repeat Hb A 2 • Consider B12/folate deficiency, drugs, liver disease/alcohol or HIV infection (Alperin et al , 1977; Galacteros et al , 1993; Howard et al , 2005; Wilkinson et al , 2007). …”
Section: Laboratory Methodsmentioning
confidence: 99%